1978
DOI: 10.1111/j.1532-5415.1978.tb03680.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypertension in the Elderly with Pindolol and Clopamide

Abstract: After a 2-week washout period, 30 elderly hypertensive patients were treated with pindolol (a beta-adrenergic blocker) for 3 weeks. In 13 patients the reduction in blood pressure was satisfactory and treatment with pindolol was continued for another 4 weeks. In 17 patients the subsequent treatment was supplemented with clopamide (a diuretic) for 4 weeks; in 6 the results were satisfactory. Side effects were few and mild.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…In 2 patients the complaints were transient at the beginning of the treatment. Five patients from the atenolol group had complaints consisting of tiredness ( 2 1 , cold extremities (11, nausea (1) and impotence (1). Also here the complaints in two cases were transient .…”
Section: Spontaneous Complaintsmentioning
confidence: 86%
“…In 2 patients the complaints were transient at the beginning of the treatment. Five patients from the atenolol group had complaints consisting of tiredness ( 2 1 , cold extremities (11, nausea (1) and impotence (1). Also here the complaints in two cases were transient .…”
Section: Spontaneous Complaintsmentioning
confidence: 86%
“…Longitudinal survey of healthy geriatric home residents (ages [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] followed 10 years.…”
Section: Retrospective Practice Analysis Of Diastolic Hypertension Comentioning
confidence: 99%
“…Although the number of elderly was small and the medication protocol not ideally flexible, the Veterans Administration Cooperative Study convincingly demonstrated a reduction in congestive heart failure, angina, and stroke in elderly patients treated for diastolic hypertension (31). The Hypertension Detection and Follow-up Program also showed a definite reduction in mortality from all causes in patients aged [60][61][62][63][64][65][66][67][68][69] treated with a rigorous stepped-care approach (32). Other studies support these findings (Tables 4, 5) (33-37).…”
Section: Findingmentioning
confidence: 99%
See 2 more Smart Citations